PENGARUH KOMPENSASI, KARAKTERISTIK PEKERJAAN DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DEPARTEMEN QUALITY ASSURANCE DAN QUALITY CONTROL PADA PT. YASUNAGA INDONESIA DI KABUPATEN SERANG - Juwandi Juwandi; Daenulhay Kamsin (Universitas Muhammadiyah Tangerang, 2020)
The purpose from this research to find out how many effect (1) compensation to employee performance, (2) job characteristics to employee performance (3) job satisfaction to employee performance (4) compensation, job characteristics and job satisfaction together (simultaneous) to employee performance. The research method used is descriptive method and associative method. The population in this research are employees of quality assurance and quality control department as 63 people while sample in this research used jenuh sample which were taken entirely from population as 63 respondents.Based on result of this research obtained, Hypothesis 1. There is an effect between compensation to employee performance, obtained result thitung > ttabel (3,455 > 1,670) with significance level ˂ 0.05. Hypothesis 2. There is an effect between job characteristics to employee performance, obtained result thitung > ttabel (5,223 > 1,670) with significance level <0.05. Hypothesis 3. There is an effect between job satisfaction to employee performance, obtained result thitung > ttabel (3,788 > 1,670) with significance level <0.05). Hypothesis 4. Obtained result Fhitung > Ftabel (18,050 > 3,14) so H0 is rejected and H1 is accepted it means there is an effect together (simultaneous) between compensation, job characteristics and job satisfaction to employee performance of quality assurance and quality control department at PT. Yasunaga Indonesia in Serang district.